Psychogenic Nonepileptic Seizures Associated with an Eating Disorder and PTSD Are Responsive to Cognitive Processing Therapy - Gearhart, Marina G.; Brewerton, Timothy D. (Case Reports in Psychiatry, 2023)
Objective. Eating disorders (EDs) are often associated with prior histories of trauma, subsequent PTSD and related psychiatric comorbidities. There is a paucity of information about their relationship to somatic symptom disorders, specifically psychogenic nonepileptic seizures (PNES), a type of functional neurological symptom disorder or conversion disorder. Methods. We report a case of a 39-year-old bisexual female with bulimia nervosa (BN), PTSD, recurrent major depressive disorder (MDD), cannabis use disorder, and PNES who responded to integrated trauma-focused treatment during residential ED treatment using cognitive processing therapy (CPT). Symptoms of ED, PTSD, major depression, and state-trait anxiety were measured using validated assessment instruments. Results. During the course of CPT treatment, the patient’s total scores on the PTSD Symptom Checklist for DSM-5 (PCL-5) went from 59 to 26, which is below the diagnostic threshold for PTSD. In addition, she demonstrated improvements in the Eating Disorder Examination Questionnaire (EDE-Q) Global Severity score, the Eating Disorder Inventory (EDI-2) total score, the Patient Health Questionnaire (PHQ-9) total score, the Spielberger State and Trait Anxiety Inventory scores, and the Eating Disorder Quality of Life (EDQOL) total score. Furthermore, her PNES also abated, and she remained seizure free for ∼1 year following discharge with the exception of one short seizure, per report of the patient. Conclusion. The use of CPT as part of an integrated trauma-informed treatment approach during residential ED treatment was successful in a woman with PNES, BN, PTSD, MDD, and cannabis use disorder.